How Students Make Meaning from Literary Text? - Heryatun, Yayu (EDUCARE, 2013)
ABSTRACT: This research was intended to explore how students make meaning whenever they read a literary text. It employed a qualitative method to find out how students responded to literary text in meaning making, type of responses produced by students after reading a literary text, and condition where students produced those responses. It was a case study involving seven students who were taking a course of Prose and their teacher. Classroom observation, questionnaire, and interview served as the data collection method. The result of this research indicated that students responded to literary text in making meaning through multiple reading with different purposes ranging from reading for gaining general idea, reading for learning from the text to reading for searching information. In addition, the way students read a literary text was through the continuum from aesthetic reading to efferent reading. The process of making meaning was demonstrated by most students through questioning about text itself and bringing the text to their lives. Students posed questions dealing with the element of story. Responses that students produced after reading a literary text was different, vary from restatement, associative, figurative, and emotional responses. Based on these findings, it is recommended for teachers that they should be explicit in stating their expectation on what students should achieve. Meanwhile, although students themselves who provide and choose literary text, they should select literary text based on their reading skills, in case of choosing the easy ones. KEY WORDS: Meaning, reader response, literary text, aesthetic reading, efferent reading, and interaction of students and teachers in the classroom.About the Author: Yayu Heryatun, M.Pd. is a Lecturer at the English Department IAIN (Institut Agama Islam Negeri or State Islamic Religion Institute) âSultan Maulana Hasanuddinâ in Banten, Indonesia. Â For academic purposes, the author is able to be contacted via her e-mail at: yayuheryatun@yahoo.comHow to cite this article? Heryatun, Yayu. (2013). âHow Students Make Meaning from Literary Text?â in EDUCARE: International Journal for Educational Studies, Vol.6(1) August, pp.43-54. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 15, 2013); Revised (July 17, 2013); and Published (August 17, 2013).Â Â